Enhancing brand loyalty through brand architecture strategy - Ramdzan Ali, Al Amirul Eimer; Senin, Muhammad Adam (Human Resource Management Academic Research Society, 2020)
The concept of brand loyalty is a well-known topic of great interest for branding and marketing researchers due to its importance in gaining sustainable competitive advantage (SCA). Literature is prolific of works pertaining to branding architecture strategy and brand loyalty. In the current era, most of the powerful brands are aspired to achieve brand loyalty goal, hence the organizations and marketers should focus on the elements of branding which will assist the organization to achieve not just sustainable competitive advantage, but also sustainable brand loyalty among its customers. There are all together three (3) branding architecture strategies namely monolithic strategy, standalone strategy and lastly, endorsed strategy. The objective of this conceptual paper is to provide insight on the relationship of brand architecture strategies on brand loyalty.